Oxygen-regulated transcription factors and their role in pulmonary disease - Semenza Gregg L (Respiratory Research, 2000)
Abstract The transcription factors nuclear factor interleukin-6 (NF-IL6), early growth response-1 (EGR-1) and hypoxia-inducible factor-1 (HIF-1) have important roles in the molecular pathophysiology of hypoxia-associated pulmonary disease. NF-IL6 controls the production of interleukin (IL)-6 in vascular endothelial cells, which may have anti-inflammatory activity by counteracting effects of IL-1 and IL-8. EGR-1 controls the production of tissue factor by macrophages, which triggers fibrin deposition in the pulmonary vasculature. HIF-1 activates the expression of the vasoconstrictor endothelin-1 in vascular endothelial cells. Angiotensin II induces HIF-1 expression and hypertrophy of pulmonary arterial smooth muscle cells. HIF-1 might therefore have multiple roles in the pathogenesis of pulmonary vascular remodeling.